Upregulation of Superenhancer‐Driven LncRNA FASRL by USF1 Promotes De Novo Fatty Acid Biosynthesis to Exacerbate Hepatocellular Carcinoma (Adv. Sci. 1/2023). Issue 1 (4th January 2023) - Peng, Jiang‐Yun; Cai, Dian‐Kui; Zeng, Ren‐Li; Zhang, Chao‐Yang; Li, Guan‐Cheng; Chen, Si‐Fan; Yuan, Xiao‐Qing; Peng, Li
Abstract : Mechanism of Superenhancer‐Driven LncRNA Accelerating Lipid Metabolism In article number 2204711, Li Peng and co‐workers reveal the mechanism of superenhancer‐related lncRNA functioning in lipid metabolism. It can be simulated by the accelerating vehicle. LncRNA FASRL is transcriptionally driven by USF1 via its superenhancer. FASRL binding to ACACA, a fatty acid synthesis rate‐limiting enzyme, increases lipid accumulation to exacerbate HCC.